A revision of the trichostrongylid nematode Cooperia Ransom, 1907, from deer game: recent integrative research confirms the existence of the ancient host-specific species Cooperia ventricosa (Rudolphi, 1809) - Albrechtová, Martina; Kašparová, Eva Štefková; Langrová, Iva; Hart, Vlastimil; Neuhaus, Birger; Jankovská, Ivana; Petrtýl, Miroslav; Magdálek, Jan; Špakulová, Marta (Frontiers in Veterinary Science, 2024)
The trichostrongylid roundworms of the genus Cooperia, which are important in veterinary medicine, currently comprise 19 valid species that parasitise the small intestines of both free-living and domestic ruminants. Only four Cooperia spp. have been reported in Europe, namely C. oncophora, C. punctata, C. curticei and C. pectinata. In 2018–2022, 25 red deer (Cervus elaphus) and 30 sika deer (Cervus nippon) of both sexes and various ages from several distant Czech locations were parasitologically examined. Intestinal nematodes of the genus Cooperia were found only in two northern regions. Using the globally recognised key book on trichostrongylid nematodes, they were preliminarily identified as C. pectinata. However, a molecular analysis of cox2 and ITS rDNA gene sequences revealed that Cooperia sp. that parasitises Czech deer represents a separate taxon that is more closely related to C. oncophora than C. pectinata. A subsequent morphological analysis and literature survey confirmed the independence of deer Cooperia sp., as it is similar but not identical to bovid C. pectinata. Previous long-term correct identifications of bovid C. pectinata and mistaken identifications of deer Cooperia species were caused by a fundamental error in the key book mentioned above. Interestingly, the ancient trichostrongylid nematode Strongylus ventricosus from the type host red deer (Cervus elaphus) shot near Greifswald (Germany) was described by Rudolphi in 1809. Rudolphi’s type material (one male and four females) was deposited in the Museum für Naturkunde (Berlin). Later, the ancient species S. ventricosus was taken as a synonym of various Cooperia spp. Our current re-examination of the type male indicated that there is a relatively good agreement regarding the most important characteristics of S. ventricosus (i.e., the shape and size of male spicules) with our new material from Czech deer; however, Rudolphi’s type material is in a rather poor condition. The suggested resurrection of the deer Cooperia sp. in this study as Cooperia ventricosa (Rudolphi, 1809) requires verification by collecting and analysing new nematode material from the type locality in the vicinity of Greifswald.